If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 3(2x + -4) = 9 + -4 + (3x + 1) Reorder the terms: 5 + 3(-4 + 2x) = 9 + -4 + (3x + 1) 5 + (-4 * 3 + 2x * 3) = 9 + -4 + (3x + 1) 5 + (-12 + 6x) = 9 + -4 + (3x + 1) Combine like terms: 5 + -12 = -7 -7 + 6x = 9 + -4 + (3x + 1) Reorder the terms: -7 + 6x = 9 + -4 + (1 + 3x) Remove parenthesis around (1 + 3x) -7 + 6x = 9 + -4 + 1 + 3x Combine like terms: 9 + -4 = 5 -7 + 6x = 5 + 1 + 3x Combine like terms: 5 + 1 = 6 -7 + 6x = 6 + 3x Solving -7 + 6x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -7 + 6x + -3x = 6 + 3x + -3x Combine like terms: 6x + -3x = 3x -7 + 3x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 -7 + 3x = 6 + 0 -7 + 3x = 6 Add '7' to each side of the equation. -7 + 7 + 3x = 6 + 7 Combine like terms: -7 + 7 = 0 0 + 3x = 6 + 7 3x = 6 + 7 Combine like terms: 6 + 7 = 13 3x = 13 Divide each side by '3'. x = 4.333333333 Simplifying x = 4.333333333
| 6*26= | | 3n+n=236 | | 5x+7x-38=95-7x | | x^2+3x+14=24 | | (3x^2)+2x-15=0 | | -7y+2=5y-7 | | y^2-3=y+9 | | 2(4x-4)+2(3x-2)=360 | | 21x^2-18x^3=6x | | -56=-49t | | 7x-4y=-26 | | 7x-2(4-3x)=3(2x+1) | | 5+7x-3x=-27 | | 3x+w=8x+v | | 53350-75h+200h=55825-150h | | 2n(n+5)= | | 7.2y+3=3y+21 | | 6-6x-3=-46+3x-14 | | -3x^2+246x-1100=0 | | 200M-75m+53350=55825-150m | | a^2+3a= | | 2e+2.6=-23 | | 7(9w)= | | 6(v+4)-2v=2(2v+1)-7 | | X+6-4x=21 | | (3x-10)+(x+40)=90 | | -4+3x+1=5x+2 | | -5-=0 | | -4x-10=7x+23 | | -18=14 | | -x-4y=-3 | | 2(xy+4)=-7 |